Agenda Reformasi Kultural Relasi Antarumat Beragama di Indonesia - Husnul Muttaqin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
The writer explores that religion, besides had ever been accused as the source of humanity crime, and has been being trusted by people to realize the humanity hope better in the future. This hope of course has base because actually religion had never been teaching violence but love each other. Based on the assumption above, the writer states to all adherents of religions to prove that religion is not a source of conflict but on contrary it offers meaningful life for human in modern world. Religion is transcendental meaning offering humanity, liberation, and transcendence agendas for all human.